Prognostic Value and Potential Immunoregulatory Role of SCARF1 in Hepatocellular Carcinoma - Patten, Daniel A.; Wilkinson, Alex L.; O'Rourke, Joanne M.; Shetty, Shishir (Frontiers in Oncology, 2020)
Scavenger receptor class F member 1 (SCARF1) is thought to play an important role in the selective recruitment of CD4+ T cells to liver sinusoidal endothelial cells during chronic liver disease. However, the contribution of SCARF1 to hepatocellular carcinoma (HCC) is currently unknown. We utilised publically-available RNA-sequencing data from The Cancer Genome Atlas (TGCA) to explore SCARF1 expression in HCC and correlated it with a number of clinicopathological features. Flow adhesion assays were used to determine the role of SCARF1 in CD4+ T cell subset recruitment. SCARF1 expression was downregulated in HCC tumour tissues, compared to non-tumoural tissues, and loss of SCARF1 expression was associated with poorly differentiated/aggressive tumours. Additionally, higher SCARF1 expression in HCC tumour tissues was highly prognostic of better overall, disease-free and progression-free survival. SCARF1 within HCC was largely associated with tumour endothelial cells and adhesion studies suggested that it played a role in the specific recruitment of proinflammatory CD4+ T cells (CD4+CD25-) to HCC tumour tissues. Endothelial SCARF1 expression in tumour biopsies may provide critical prognostic information. Additionally, SCARF1 may also be a novel endothelial target that could help re-programme the microenvironment of HCC by promoting effector T cell tumour infiltration.